Foot Reflexology And Back Massage Reduce Fatigue Levels In Chronic Kidney Disease: Literature Review - Mampesi, Anastasia; Muhith, Abdul; Zahro, Chilyatiz (Journal of Applied Nursing and Health, 2023)
Background: Chronic Kidney Disease(CKD) is a disease that disrupts kidney function and cannot be recovered. The body's inability to maintain metabolism and fluid and electrolyte balance results in an increase in urea Tnon-pharmacological therapy that can be used for patients with Chronic Kidney Disease(CKD)To reduce fatigue, namely foot reflexology and back massage. To find out the implementation of foot reflexology and back massage to overcome the nursing problem of fatigue related to physiological conditions in patients with Kidney Disease(CKD) Methods: Writing this scientific paper uses the research method used in this research, namely, a literature review with the type of study to be identified, namely, a case report. Results: Research was conducted on patients diagnosed with Kidney Disease(CKD). The results of the study showed that the intervention of Foor Reflexology and Back Massage techniques was carried out for two days twice a day; on the first day before the intervention, the fatigue level score was 33 (Severe Fatigue), and after the intervention, the fatigue level score was 14 (Mild Fatigue). ) The second day before the intervention, a fatigue level score 24 (Moderate Fatigue) was obtained. After the intervention, a fatigue level score of 13 (mild fatigue) was obtained. Conclusion: This research shows that foot reflexology and back massage therapy can reduce fatigue in chronic Kidney Disease(CKD) patients.